W poszukiwaniu odpowiedzi na pytanie - Czy nauczyciele gimnazjum kształtują postawę ekologiczną swoich wychowanków? - Małgorzata Stańczak (Studia Ecologiae et Bioethicae)
In order to survive humankind needs ecological education in accordance with the rule of well-balanced development. The phenomenon involves all educational processes. We need well-qualified teachers in order to mobilize pupils for proper action, influence their interests and higher level of knowledge or shape ecological awareness, these teachers link the world of thoughts and general consciousness.